Strategi Pembelajaran Berbasis Kearifan Lokal sebagai Upaya Penguatan Pendidikan Karakter di Era Globalisasi (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
The globalization era can cause cultural homogeneity. Cultural homogeneity if not addressed properly, will have an impact on the decline in the quality of the character of the younger generation. The decline in the quality of the character of the younger generation has led to the emergence of many behaviors that are not in accordance with applicable norms, such as fraud and crime. This study aims to examine local wisdom-based learning strategies as an effort to strengthen character education in the globalization era. The result of this study is that the local wisdom-based learning strategy is carried out using the self-directed learning method. There are four stages of the implementation of learning strategies that can be implemented, namely the planning stage, the implementation stage, the supervision stage, and the assessment stage. Things that need to be prepared by the school to implement this learning strategy are administration, cooperation or partners, and infrastructure.